Mitochondrial genome study of Camellia oleifera revealed the tandem conserved gene cluster of nad5–nads in evolution - Gu, Yiyang; Yang, Liying; Zhou, Junqin; Xiao, Zhun; Lu, Mengqi; Zeng, Yanling; Tan, Xiaofeng (Frontiers in Plant Science, 2024)
Camellia oleifera is a kind of high-quality oil supply species. Its seeds contain rich unsaturated fatty acids and antioxidant active ingredients, which is a kind of high-quality edible oil. In this study, we used bioinformatics methods to decipher a hexaploid Camellia oil tree’s mitochondrial (mt) genome based on second-generation sequencing data. A 709,596 bp circular map of C. oleifera mt genome was found for the first time. And 74 genes were annotated in the whole genome. Mt genomes of C. oleifera and three Theaceae species had regions with high similarity, including gene composition and gene sequence. At the same time, five conserved gene pairs were found in 20 species. In all of the mt genomes, most of nad genes existed in tandem pairs. In addition, the species classification result, which, according to the gene differences in tandem with nad5 genes, was consistent with the phylogenetic tree. These initial results provide a valuable basis for the further researches of Camellia oleifera and a reference for the systematic evolution of plant mt genomes.